FACTOR ANALYSIS OF DEMAND FOR INDONESIAN NICKEL EXPORTS IN EUROPE - Ramadhan Razali; Fuadi; Rico Nur Ilham; Falahuddin; Rahmaniar (PT. Radja Intercontinental Publishing, 2024)
The purpose of this study is to determine the demand factors for Indonesian nickel exports in Europe. Regarding the formulation of the problem in this study, what are the factors for the demand for Indonesian nickel by Europe. Although the research method used is qualitative. Based on the results of this study it can be concluded that Nickel is a silvery-white hard metal with a slight luster of gold pattern. Nickel itself is a metal that is strong, dense, durable, heat and corrosion resistant. In addition, nickel is also a metal with good conductors of electricity and heat and one of the four very important metal elements because this metal is ferromagnetic or can be said to be easily magnetized at certain room temperatures. Therefore, nickel has a variety of uses that can be utilized in a variety of products. One of them is the raw material for making cables. Nickel is a scarce natural resource, therefore countries that do not have this natural resource must import it from producing countries. At the same time, producing countries must ensure that there are no shortages.